Digital Economy for the Supply Chain as Indicator of Competitiveness of the Cites - Aidar Gamisovich Sharifullin; Guzel Rachitovna Safina; Viktoria Alekseevna Fedorov; Anna Alikseevna Kurzhanova (International Journal of Supply Chain Management, 2019)
The current state of development of world urbanistic community shows that the main accents in competitive interdependence between basic subsystems of territories are transferred from nation-wide - the national level on more local-regional and local: cities and city systems. One of the main technology management for supply chain is digital technology. The digital economy which key factor of production data in a digital form - digital technologies act gives great opportunities for the development of the city, acts as a factor of increase in its competitiveness. In relation to the cities of the Russian Federation, the main, most objective indicators of competitiveness are productivity (efficiency), employment, the standard of living, quality of the urban environment. Introduction of the digital economy is accompanied by a number of risks. In relation to the cities and agglomerations, it is necessary to provide actions for minimization of the risks connected with a problem of creation of the corresponding infrastructure. Digitalization potentially influences the majority of parameters of quality of the urban environment and promotes improvement of quality of life of citizens: welfare and employment, level of expenses, education level and human capital, existence of free time and nature of its use, level of environmental pollution, existence and quality of social communications, general satisfaction with life.